PROMOTION OF RURAL TOURISM IN THE EU CROSS-BORDER PROGRAMME - Jovanović, Duško; Milovanović, Miloš; Lukač, Dragan (Economics of Agriculture, 2011)
The European Commission has established an unique instrument for pre-accession countries in the European integration process. Cross-border cooperation, as a component of the IPA assistance for the countries in the EU accession process is a direct continuation of strengthening cooperation with the Western Balkans countries, as candidates and potential candidates for EU membership. The project funded by the European Commission through the IPA Programme Hungary-Serbia, called INNOAXIS, makes operational development plans for the regions of northern Serbia and the southern border region of Hungary, and one of the goals of this project is the strategic development of rural tourism. The IPA component related to rural development is intended only for candidate countries, and Serbia, as a potential candidate for EU membership, has not been able to use this component.